Antimicrobial Resistance Patterns of Bacterial Isolates from Blood Culture among HIV/AIDS Patients at Felege Hiwot Referral Hospital, Northwest Ethiopia - Mohabaw Jemal; Teshiwal Deress; Teshome Belachew; Yesuf Adem (International Journal of Microbiology)
Background. The emergence and spread of antimicrobial resistance in bacteria is recognized as a global public health problem. Bloodstream infection with antimicrobial-resistant bacteria in HIV/AIDS patients makes the problem more challenging. So, regular and periodic diagnosis and use of the appropriate antimicrobial susceptibility pattern determination is the only option for decreasing the prevalence and development of drug-resistant bacteria. Methods. An institution-based cross-sectional study was conducted among 384 HIV/AIDS patients. Sociodemographic data of patients were recorded using structured questionnaires. Blood cultures were collected with BACTEC aerobic blood culture bottles. A pair of samples was collected from each patient aseptically and incubated at 37°. If samples are positive for bacterial agents, they were subcultured to solid media such as blood agar plate, chocolate agar plate, and MacConkey agar plates. Identification was performed using colony characteristics and standard biochemical techniques. The antimicrobial susceptibility test was determined by the Kirby–Bauer disc diffusion method. Data entry and analysis were performed while using SPSS version 20. Descriptive statistics were performed to calculate frequencies. Results. Altogether, 384 patients were included, and 123 blood cultures were positive, so that the yield was thus 32%. About 46 (37.4%) of Gram-negative and 77 (62.6%) of Gram-positive bacterial species were identified. Among Gram-negative bacterial isolates, K. pneumoniae was the leading pathogen, 19 (41.3%), whereas S. aureus, 38 (49.4%), was predominant among Gram-positive isolates. In his study, the majority of Gram-positive isolates showed high level of resistance to penicillin, 72 (95.5%), tetracycline, 55 (71.4%), and cotrimoxazole, 45 (58.4%). About 28 (73.6%) of S. aureus isolates were also methicillin-resistant. Gram-negative bacterial isolates also showed a high resistance to ampicillin (91.3%), tetracycline (91.3%), and gentamicin (47.8%). Overall, about 78% of multidrug resistance was observed. Conclusion. Several pathogens were resistant to greater than five antimicrobial agents, so that proper management of patients with bacteremia is needed, and a careful selection of effective antibiotics should be practiced.